Degassing regime of Hekla volcano 2012-2013 - Ilyinskaya, E.; Fridriksson, T.; Óladóttir, A.; Óskarsson, F.; Grassa, F.; Pfeffer, M.; Lechner, K.; Yeo, R.; Giudice, G.; AIUPPA, Alessandro; BERGSSON, Baldur; DI NAPOLI, Rossella (Geochimica et Cosmochimica Acta, 2015)
Hekla is a frequently active volcano with an infamously short pre-eruptive warning period. Our project contributes to the ongoing work on improving Hekla's monitoring and early warning systems. In 2012 we began monitoring gas release at Hekla. The dataset comprises semi-permanent near-real time measurements with a MultiGAS system, quantification of diffuse gas flux, and direct samples analysed for composition and isotopes (δ 13 C, δD and δ 18 O). In addition, we used reaction path modelling to derive information on the origin and reaction pathways of the gas emissions.Hekla's quiescent gas composition was CO 2 -dominated (0.8mol fraction) and the δ 13 C signature was consistent with published values for Icelandic magmas. The gas is poor in H 2 O and S compared to hydrothermal manifestations and syn-eruptive emissions from other active volcanic systems in Iceland. The total CO 2 flux from Hekla central volcano (diffuse soil emissions) is at least 44Td -1 , thereof 14Td -1 are sourced from a small area at the volcano's summit. There was no detectable gas flux at other craters, even though some of them had higher ground temperatures and had erupted more recently. Our measurements are consistent with a magma reservoir at depth coupled with a shallow dike beneath the summit. In the current quiescent state, the composition of the exsolved gas is substantially modified along its pathway to the surface through cooling and interaction with wall-rock and groundwater. The modification involves both significant H 2 O condensation and scrubbing of S-bearing species, leading to a CO 2 -dominated gas emitted at the summit. We conclude that a compositional shift towards more S- and H 2 O-rich gas compositions if measured in the future by the permanent MultiGAS station should be viewed as sign of imminent volcanic unrest on Hekla.